中国社会转型期城镇贫困问题研究 = Urban poverty problem in China's transitional economy - 潘爱良 Pan, Ailiang (2008)
After Chinese society accessing the transformation period, urban poverty problem has been standing out and getting more and more attentions from the government and individual. This paper analyzes the multi-level reasons that induce the produce and development of this problem and the harm if the problem cannot be solved immediately, and present some pertinent policy suggestions.